IMPLIKASI PILKADA LANGSUNG TERHADAP PERTANGGUNGJAWABAN KEPALA DAERAH DALAM PENYUSUNAN PROGRAM PEMBANGUNAN DAERAH - Hakim, Lukman (Jurnal Konstitusi, 2010)
The main objective of this study is to find the implication of the election regional government system. responsibility in regional government system is extremely vital on establishing regional government. It is analyzed from the character and kind of responsibility. The character and kind of responsibility not only has juridical meaning, but also has philosophical meaning in the context of Indonesian philosophy, which is reflected in governmental system of Indonesian Republic Unity State. Constitutional base, variety, maintaining and developing the real governmental principles, and law state basis are the primary pillars in determining the character and kind of responsibility in regional government system.  Responsibility concerning its position in regional government system that keep refer to the system of regional household. Responsibility is vital in establishing the governance is oriented to the principles of regional government establishment that includes general principles of good government and the principle of good governance. Beside that, the responsibility and accountability in the context of state administration and the aspect of public service as well. The principle and system of managing the distribution of regional matters, changes on managing the establishment of regional autonomy, and urgency of the development on the future of nation and Indonesian Republic Unity State.